Carbon inverse opal entrapped with electrode active nanoparticles as high-performance anode for lithium-ion batteries - Huang, Xin (2013)
Enhancing ion and electron transport kinetics together with improving cycle life are important issues to be considered when developing high-performance Li ion batteries. Here we demonstrate a three dimensional ordered macroporous conductive electrode concept by entrapping electrode active nanoparticles in an interpenetrating macroporous carbon inverse opal. The electrodes are featured with simultaneously enhanced ion and electron transport kinetics as well as geometrically constrained active nanoparticles. The electrode can deliver up to 94.17% of theoretical capacity over 1000 discharge/charge cycles at a current density of 2.0 A g−1, and exhibits good rate capability in the high current density range of 1.0–10.0 A g−1. We hope that our findings will help pave the way for tailored design of many other sophisticated electrode materials in electrochemistry.